2009
DOI: 10.1186/1746-1596-4-41
|View full text |Cite
|
Sign up to set email alerts
|

Altered PTEN expression; a diagnostic marker for differentiating normal, hyperplastic and neoplastic endometrium

Abstract: BackgroundDifferent molecular alterations have been described in endometrioid endometrial carcinoma (EECA). Among them the most frequently altered is loss of the PTEN protein, a tumor suppressor gene. The purpose of this study was to evaluate the expression pattern of PTEN gene in normal, hyperplastic and neoplastic endometrium.MethodsIn a study in a referral gynecologic hospital in Tehran, Iran, immunohistochemical (IHC) evaluation of PTEN was performed on 87 consecutive specimens to the following three group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
56
4
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 28 publications
10
56
4
1
Order By: Relevance
“…21 In a few studies, PTEN immunohistochemical expression patterns have been reported to have utility as a diagnostic marker for differentiating normal, hyperplastic and neoplastic endometrium. 8,42,43 Pavlakis et al 44 suggested that PTEN-loss and nuclear atypia of EIN in endometrial biopsies can predict the existence of a concurrent endometrial CA. However, some other studies have failed to show that lack of PTEN expression has the specificity and reproducibility to be clinically useful as a biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…21 In a few studies, PTEN immunohistochemical expression patterns have been reported to have utility as a diagnostic marker for differentiating normal, hyperplastic and neoplastic endometrium. 8,42,43 Pavlakis et al 44 suggested that PTEN-loss and nuclear atypia of EIN in endometrial biopsies can predict the existence of a concurrent endometrial CA. However, some other studies have failed to show that lack of PTEN expression has the specificity and reproducibility to be clinically useful as a biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…Inactivation of PTEN, a major negative regulator of the PI3K pathway has been associated with the development of EC in mouse knockout and human observational studies (Mutter 2001, Kandoth et al 2013. Loss of PTEN expression was suggested to be partly associated with the ECs through a premalignant phase and described as an early event in endometrial tumorigenesis (Sarmadi et al 2009). Interestingly, high dose progestin therapy has been shown to reverse pre-existing PTEN inactivated endometrial latent precursors and endometrial hyperplasia in some women (Orbo et al 2006).…”
Section: Cell Signaling Pathwaysmentioning
confidence: 99%
“…It was shown that ctDNA level increased in advanced stage of ovarian cancers compared to controls, so ctDNA quantity can be useful for noninvasive screening and this disease surveillance [143]. Although point mutations have been extensively studied, chromosomal rearrangements have confirmedsuperior tumor specificity [144,145]. A panel of individualized junctions consequent from tumor DNA possibly will be an useful way to monitor cancer patients for relapse and therapeutic efficacy using ctDNA [144].…”
Section: Thyroid Tumorsmentioning
confidence: 99%